Superalloys 2012 2012
DOI: 10.1002/9781118516430.ch53
|View full text |Cite
|
Sign up to set email alerts
|

Physics‐Based Modeling of Thermo‐Mechanical Fatigue in PWA 1484

Abstract: Thermomechanical fatigue (TMF) is a common damage process incurred by superalloys used for turbine components. Life modeling of TMF in superalloys has traditionally looked to phenomenological approaches for coupling the environmentalfatigue interactions occurring during TMF loading. While these approaches provide good predictive results within the range of test variables studied, they are not easily extrapolated to other conditions. A life model has been developed for single crystal Nibase superalloys experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…These components are often cast from nickel-base superalloys in the form of singlecrystals. The material anisotropy of single-crystal materials adds an extra dimension of complexity to the modelling, testing and understanding of the fracture mechanisms [3][4][5][6][7][8][9][10][11]. The service life of many hot components is not fully restricted by the number of cycles to crack initiation, which means that a certain amount of crack propagation is allowed before the component has to be replaced in service.…”
Section: Zusammenfassungmentioning
confidence: 99%
“…These components are often cast from nickel-base superalloys in the form of singlecrystals. The material anisotropy of single-crystal materials adds an extra dimension of complexity to the modelling, testing and understanding of the fracture mechanisms [3][4][5][6][7][8][9][10][11]. The service life of many hot components is not fully restricted by the number of cycles to crack initiation, which means that a certain amount of crack propagation is allowed before the component has to be replaced in service.…”
Section: Zusammenfassungmentioning
confidence: 99%
“…The loads 4 are not in phase with the strains and this situation is referred to as TMF, as explained earlier. In recent years, research aimed ultimately at developing a life prediction methodology has been carried out in our laboratories and the evolution of this work has been reported in numerous publications [72][73][74][75][76][77][78][79][80]. The most important findings are reprised in this section but it is appropriate to note that the work was motivated, in part, by simple experiments designed to simulate TMF in René 80 [78,80].…”
Section: Environment-fatigue Interactions In Thermo-mechanical Fatiguementioning
confidence: 99%
“…The inherent crystallographic structure of single-crystal nickel-base superalloys results in a complex material behaviour, which leads to many challenges in testing, modelling and prediction of the crack initiation and growth be-haviour [2][3][4][5][6][7][8]. It has frequently been observed that two distinct cracking modes are present in these materials; crystallographic cracking on the octahedral {111}planes and Mode I cracking perpendicular to the loading direction [9][10][11][12][13][14], cf.…”
Section: Introductionmentioning
confidence: 99%